Perlindungan Hukum Terhadap Penghuni Rusunawa dalam Pelaksanaan Perjanjian Sewa Menyewa dI Sumatera Barat - Andalusia, Andalusia Andalusia; Elmis, Linda Elmis; Pratama, Arya Putra Rizal (Simbur Cahaya, 2022)
The house is one of the basic needs of every person in addition to the need for food (food) and clothing (clothing). The need for a house as a place to live or stay in urban areas is very large along with the large number of residents. The construction of flats is part of the government's policy in poverty alleviation and welfare for the lower middle class. The construction of simple rental flats (rusunawa) is intended for low-income people (MBR). Placement for prospective residents of Rusunawa has terms and conditions through contractual legal grounds. This becomes a skill and is right on target that the purpose of building rusunawa is only for the lower middle class. This study uses an empirical juridical method (empirical legal research) with an analytical approach (conceptual approach) and is descriptive. The results of this study explain that, the occupants of the Rusunawa in Sawahlunto carry out the rental agreement. For the placement of the residents using a written agreement (contract) for a period of 1 (one) year with an extension through applicable terms. Then, there is the implementation of an obstacle in the rental agreement in the form of arrears in rent payments, however, a written warning will be taken as a form of firm warning. The form of legal protection has been carried out well through quick response actions if there are problems experienced by residents, both facilities, facilities and infrastructure to the utilization of residents' facilities for flats through the permission of the local UPTD Rusunawa Head.